Influence of Conditional Cash Transfers on the Uptake of Maternal and Child Health Services in Nigeria: Insights From a Mixed-Methods Study - Ezenwaka, Uchenna; Manzano, Ana; Onyedinma, Chioma; Ogbozor, Pamela; Agbawodikeizu, Uju; Etiaba, Enyi; Ensor, Tim; Onwujekwe, Obinna; Ebenso, Bassey; Uzochukwu, Benjamin; Mirzoev, Tolib (Frontiers in Public Health, 2021)
Background: Increasing access to maternal and child health (MCH) services is crucial to achieving universal health coverage (UHC) among pregnant women and children under-five (CU5). The Nigerian government between 2012 and 2015 implemented an innovative MCH programme to reduce maternal and CU5 mortality by reducing financial barriers of access to essential health services. The study explores how the implementation of a financial incentive through conditional cash transfer (CCT) influenced the uptake of MCH services in the programme. Methods: The study used a descriptive exploratory approach in Anambra state, southeast Nigeria. Data was collected through qualitative [in-depth interviews (IDIs), focus group discussions (FGDs)] and quantitative (service utilization data pre- and post-programme) methods. Twenty-six IDIs were conducted with respondents who were purposively selected to include frontline health workers (n = 13), National and State policymakers and programme managers (n = 13). A total of sixteen FGDs were conducted with service users and their family members, village health workers, and ward development committee members from four rural communities. We drew majorly upon Skinner's reinforcement theory which focuses on human behavior in our interpretation of the influence of CCT in the uptake of MCH services. Manual content analysis was used in data analysis to pull together core themes running through the entire data set. Results: The CCTs contributed to increasing facility attendance and utilization of MCH services by reducing the financial barrier to accessing healthcare among pregnant women. However, there were unintended consequences of CCT which included a reduction in birth spacing intervals, and a reduction of trust in the health system when the CCT was suddenly withdrawn by the government. Conclusion: CCT improved the utilization of MCH, but the sudden withdrawal of the CCT led to the opposite effect because people were discouraged due to lack of trust in government to keep using the MCH services. Understanding the intended and unintended outcomes of CCT will help to build sustainable structures in policy designs to mitigate sudden programme withdrawal and its subsequent effects on target beneficiaries and the health system at large.